Partial inhibition of the human immunodeficiency virus type 1 protease results in aberrant virus assembly and the formation of noninfectious particles. - Kaplan, A H (1993)
The production of infectious particles by human immunodeficiency virus type 1 is dependent on the accurate cleavage of its Gag and Gag/Pol precursors by a virally encoded protease. In the absence of protease activity, morphologically abnormal particles which are noninfectious are formed. Recently, inhibitors of the protease of human immunodeficiency virus type 1 have been developed as potential therapeutic agents. We have examined the basis for the loss of infectivity at the limiting inhibitor concentrations that are likely to be achieved in clinical settings. We found that subtle defects in processing are correlated with profound deficits in infectivity. Further, we correlated this partially disrupted processing with an altered virion morphology. These data suggest that accurate and complete processing is essential to the formation of infectious, morphologically normal virions and that the pathway by which these precursors are processed and assembled is sensitive to partial inhibition of the protease by an inhibitor disproportionate to the effect of the inhibitor on the viral protease itself.